Effects of Various Mixed Metal ChloridesAlCl3 in TiCl4/MgCl2/THF Catalytic System on Ethylene Polymerization - Nittaya Sudsong; Wanna Phiwkliang; Bunjerd Jongsomjit; Piyasan Praserthdam (ASEAN Journal of Chemical Engineering, 2014)
In this research, the modification of TiCl4/MgCl2/THF catalyst system with various metal chlorides was investigated on ethylene polymerization. Experimentally, metal chlorides (CaCl2, FeCl2 and ZnCl2) were simultaneously introduced different with TiCl4/MgCl2/THF catalyst. ICP analysis was used to determine the total amount of each metal in the catalyst. For polymerization reaction, TEA was used as cocatalyst and hexane was used as a medium solvent. The Al/Ti molar ratio was 140. The activity result of Ca-Al, Zn-Al and Fe-Al was 979, 1009 and 1476 kgPE/molTi.h, respectively. The coaddition of AlCl3 and FeCl2 in TiCl4/MgCl2/THF catalyst system exhibited the highest activity. It suggested that the co-addition of AlCl3 and FeCl2 has higher electronegativity (EN) and the radius of Fe2+ is closer to Mg2+ resulting in an increased efficiency of the THF removal. This result led to improve the catalyst performance.